Technology of obtaining and chemical profiles of dry extracts from leaves of prospective species of the hawthorn genus - Sydora, N.; Yakovenko, V.; Ochkur, O.; Rudnyk, A.; Honcharov, O.; Zuikina, S.; Romas, K.; Marchenko, M.; Рудник, Анна Михайлівна (My University, 2023)
The aim of the work was to develop a technology for obtaining dry extracts from leaves of non-pharmacopoeia species of hawthorn and establishing their chemical profiles. Materials and methods. Leaves of Crataegus mollis Sarg., Crataegus submollis Sarg. and Crataegus arnoldiana Sarg., used to obtain the dry extracts, were harvested in the Botanical Garden of the National University named after M. N. Karazina in August 2021. To determine the chemical profiles of the obtained dry extracts, the spectrophotometric method and the high-performance liquid chromatography (HPLC) method were used. Results. A technological scheme for obtaining dry extracts of hawthorn leaves has been developed. The content of flavonoids and hydroxycinnamic acids in dry extracts of the leaves of C. mollis Sarg., C. submollis Sarg. and C. arnoldiana Sarg. was determined. The content of free amino acids in extracts ranges from 0.70 % to 0.99 %. The content of flavonoids ranged from 7.25 %±0.04 to 8.43 %±0.01, of hydroxycinnamic acids – from 2.35 %±0.02 to 2.85 %±0.03. Rutin, kaempferol-3-O-glycoside, epicatechin and chlorogenic acid were identified in all extracts by the HPLC method. In dry leaf extracts of C. arnoldiana Sarg. and C. mollis identified p-coumaric acid; C. arnoldiana Sarg. – quercetin; C. arnoldiana Sarg. and C. submollis Sarg. – ferulic acid; C. submollis Sarg. and C. mollis Sarg. – quercetin-3-O-rhamnoside. Conclusions. Dry leaf extracts of C. mollis Sarg., C. submollis Sarg. and C. arnoldiana Sarg. were obtained. For the first time, the content of flavonoids and hydroxycinnamic acids in the extracts was determined by HPLC. It was established that the chemical profile of the obtained extracts is formed by rutin, chlorogenic acid and kaempferol- 3-O-glycoside, which can be used in further standardization of these substances. In addition, a comparative study of the amino acid composition of the obtained extracts was carried out for the first time
Keywords: hawthorn; leaves; dry extracts; chemical profile; technology; flavonoids; hydroxycinnamic acids; amino acids